Three-Dimensional Dual-Energy Computed Tomography for Enhancing Stone/Stent Contrasting and Stone Visualization in Urolithiasis - El-Sayed H. Ibrahim; William E. Haley; Maria A. Jepperson; David D. Thiel; Michael J. Wehle; Joseph G. Cernigliaro (Case Reports in Urology)
The use of dual-energy computed tomography (DECT) for evaluating urinary calculi has been appreciated due to the modality’s capability of differentiating between uric acid (UA) and non-UA stones, which are color coded based on a postprocessing algorithm. No other imaging modality or laboratory test is able to identify the stone composition without first attaining the stone material. Knowledge of the stone composition is clinically significant since UA calculi may be treated medically whereas non-UA calculi may require surgical removal. Regardless of the stone type, ureteral stents are often placed to prevent or treat obstruction. Recent work has demonstrated that commonly used stents are also colored based on their dual energy characteristics and may thereby either improve or obscure the identification of adjacent calculi. Herein, we report the case of a 65-year-old man who underwent percutaneous nephrolithotomy of a large staghorn stone with subsequent significant residual stone fragments noted on a follow-up scan. By using three-dimensional DECT and taking advantage of color contrasting, the stone composition, burden, shape, and boundary were clearly depicted apart from the adjacent stent, resulting in successful medical treatment and obviating the need for further surgical intervention.